STUDY OF THE STATE OF THE SCIENTIFIC AND METHODOLOGICAL EQUIPMENT FOR FORMING REQUIREMENTS TO THE CHARACTERISTICS OF NOISE FROM A SHOT FROM A SMALL WEAPON - Bilenko, Oleksandr; Pistryak, Petro; Martynov, Ihor (Honor and Law, 2021)
The work provides the results of the analysis of foreign and national scientific articles, dissertation research and interstate standards on how valid they are for the formation of requirements for the noise characteristics of small arms fire in order to ensure the covert performance of fire mission carried out by security forces. A particular problem is that the development of RSLS device (reduction of the sound level of the shot device) serves for the tasks of the defense forces or by enterprises on their initiative. Surpassing competitors on a set of indicators is often enough to increase sales which is the main purpose of such manufacturers. Thus, manufacturers emphasize on the characteristics of competitors, leaving aside the needs of law enforcement agencies, including security forces. Moreover, it is not completely specified what methods indicating shot noise are determined in each case, and occasionally the indicators themselves are not still determined. There is a quite large range of objective indicators to describe the sound field of the shot noise. These are frequency or angular frequency of the sound wave, amplitude of oscillations, oscillating speed, sound pressure, effective values of oscillating speed and sound pressure, sound intensity, sound intensity and sound pressure levels, relative levels of sound intensity and sound pressure, sound energy density, sound power, etc. Thus, the current procedure for determining the noise of the shot has not been regulated, neither have the list of its applicable characteristics. It is determined that the existing scientific papers do not let reasonably form requirements for the characteristics of the shot noise from small arms when performing fire tasks by security forces.